SISTEM INFORMASI MANAJEMEN KEUANGAN DALAM PENGELOLAAN KEUANGAN NEGARA PADA KANWIL DITJEN PERBENDAHARAAN PROVINSI SULAWESI TENGGARA - Aminuddin; Akhyar Abdullah; Clara Nella (Halu Oleo University, 2023)
This study aims to determine the application of management information systems in state financial management and financial management at the Regional Office of the Directorate General of Treasury of Southeast Sulawesi Province. This research uses qualitative methods with descriptive research types. Data analysis techniques in this study are data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that the integrated system in the SAKTI application has an impact on saving time for the financial management process. The SAKTI application also has a high level of security because it uses One Time Password (OTP). Although the SAKTI application is still classified as a new application, its application is very effective and optimal and facilitates the financial management process. Financial management at the Regional Office of the Directorate General of Treasury of Southeast Sulawesi Province is very efficient and the SAKTI application is used for all management processes ranging from planning, recording to accountability.